Deep Map Country : Literary Cartography of the Great Plains - Maher, Susan Naramore (Book collections on Project MUSE., 2014)
"Scholarly study of Great Plains nonfiction writers in the genre of "deep mapping", a genre that weaves together strata of narrative that includes natural history, cultural history, geography, memoir, and inter-textual material"--